2020
DOI: 10.1002/nop2.449
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on patient safety culture among emergency nurses in the public and private hospitals of Tabriz, Iran

Abstract: Aim To appraise patient safety culture in emergency departments of Iranian public and private hospitals. Design A comparative cross‐sectional survey design was used. Methods This cross‐sectional study was conducted from January–March 2019. For data collection, the Hospital Patient Safety Culture (HSOPSC) questionnaire was employed. The study sample comprised 256 participants. Independent t test and analysis of variance were performed to report the mean differences in total patient safety culture perception acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
1
12
3
4
Order By: Relevance
“…En su mayoría, están relacionados con el ambiente y área clínica asistencial; y cabe recalcar que mientras exista un paciente se puede presentar un evento adverso y disminuir la calidad de la atención en salud. Debido a esto el objetivo en común para mejorar la cultura de seguridad del paciente es minimizar los errores relacionados con la atención en salud a nivel mundial [10][11] .…”
Section: Introductionunclassified
“…En su mayoría, están relacionados con el ambiente y área clínica asistencial; y cabe recalcar que mientras exista un paciente se puede presentar un evento adverso y disminuir la calidad de la atención en salud. Debido a esto el objetivo en común para mejorar la cultura de seguridad del paciente es minimizar los errores relacionados con la atención en salud a nivel mundial [10][11] .…”
Section: Introductionunclassified
“…In third world and developing countries, accurate estimates are difficult because with no effective recording and reporting systems, there is a shortage of research information. However, it is thought that the medical errors rate is high [7]. In Iran, it is estimated that between 3 and 17% of in-patients experience unwanted side effects as a result of medical errors with 30-70% of these being preventable [8].…”
Section: Introductionmentioning
confidence: 99%
“…Like this study, those two studies also reported that the “nonpunitive response to error” dimension was the weakest dimension. Other studies have also found no difference in perceptions of the safety culture in public and private hospitals in countries with economic development status similar to Brazil (Chegini et al , 2020).…”
Section: Discussionmentioning
confidence: 84%